Using Proton Nuclear Magnetic Resonance (NMR) as a calibrating reference for magnetic field measurement instruments: Sensitive volume and magnetic field homogeneity. (February 2020) - Rodriguez, Gonzalo G.; Forte, Guillermo; Anoardo, Esteban
Graphical abstract: Highlights: The role of the magnetic field inhomogeneity in NMR as a calibrating reference for magnetic metrology is discussed. Two different approaches to treat this aspect are presented. 1-A method based on the analysis of the Fourier Transform of the NMR ECHO signal. 2-A method including additional hardware (Magnetic Field Profiler or MFP) to compensate for magnetic field inhomogeneity. Both methods are compared with real measurements. Abstract: Nuclear magnetic resonance can be conveniently used to set up reference values of magnetic flux densities for the calibration of measurement instrumentation. Two measurement procedures are proposed based on the Fourier analysis of the nuclear magnetic signal. Particularly, we consider the situation where the reference magnetic flux density may change its value across the sensor active area/volume due to spatial inhomogeneities. An explored potential solution uses an electronic compensation system in order to minimize the spatial inhomogeneities of the magnetic flux density within the calibrating volume. For this purpose, a previously designed device was added to the magnetic resonance apparatus. Both methods allow a performance better than 10 ppm in calibrating measurements by using a magnetic flux density source of the order of 100 ppm in spatial homogeneity within the calibrating volume. Examples of both methods are discussed.